Effect of Short Term Oral Administration of Silymarin on Healing of Colonic Anastomosis in Rats - Mozhgan Malekolkalami; Mehdi Behfar; Ali-Asghar Tehrani (Iranian Journal of Veterinary Surgery, 2020)
Objective- Leakage after colon anastomosis is the most common complication with the highest mortality rate. Silymarin possesses potent anti-inflammatory, antioxidant, reparative and antibacterial activities and therefore has been used to accelerate different experimental wound healing models. This study was aimed to investigate effects of orally administered silymarin following colonic resection and anastomosis in terms of histopathological and mechanical parameters. Design- An experimental study.Animals- Twenty four male mature Wistar ratsProcedures- The rats were divided randomly into two groups. After aseptic preparation, descending colon was exteriorized thorough laparotomy. Then, colon resection and end to end anastomosis was performed in all rats. The control rats were gavaged with 1 ml normal saline post operatively as placebo while the rats in the treatment group received 50 mg/kg silymarin suspended in 1 ml normal saline for five consecutive days. At the 7th day, all rat were euthanized. Results- Necropsy finding showed that leakage, adhesion formation and peritonitis scores in treatment group were significantly decreased. On histopathology, decreased inflammatory cell infiltration was observed in the treatment group. While, the scores of angiogenesis, cell proliferation, and collagen deposition were significantly increased in the treatment group. No significant difference was observed in bursting pressure when control samples were compared to the silymarin treated ones. Furthermore, mechanical properties (including: maximum load, yield load, and absorbed energy) in treatment group were significantly increased compared to control group. Conclusion and Clinical Relevance- The results of the present study showed that oral administration of silymarin following colonic anastomosis in rats improves the structural indices of wound healing and its mechanical characteristics with lower rates of anastomotic complications.